Differential Reinforcement of Low Rate Schedules Reduce Severe Problem Behavior. Issue 5 (September 2018) - Bonner, Andrew C.; Borrero, John C.
Differential-reinforcement-of-low-rate (DRL) schedules are reinforcement contingencies designed to reduce response rates. A common variation of the DRL arrangement is known as full-session DRL ( f -DRL), in which a reinforcer is presented at the end of an interval if the response rate during that interval is below a predetermined criterion. Prior human operant research involving arbitrary mouse clicks has shown that the f -DRL is likely to reduce target responding to near zero rates. Similarly, applied research has shown that the f -DRL is likely to reduce minimally disruptive classroom behavior. There are, however, relatively few successful applications of the f -DRL to severe forms of problem behavior (e.g., self-injurious behavior). Thus, the purpose of this study was to examine the effects of f -DRL on the severe problem behavior of individuals with intellectual and developmental disabilities. For four participants, the f -DRL reduced severe problem behavior by clinically significant levels. Furthermore, results of a contingency strength analysis showed a strong negative contingency strength between target responding and reinforcer delivery for all participants.